Neuropsychological Functioning Predicts Community Outcomes in Affective and Non-Affective Psychoses: A 6-month follow-up - Lewandowski, Kathryn E. (2013)
INTRODUCTION: Neurocognitive dysfunction is a major symptom feature of schizophrenia and bipolar disorder. A prognostic relationship between cognition and community outcomes is well-documented in schizophrenia and increasingly recognized in bipolar disorder. However, specific associations amongst neurocognition, diagnosis, state symptomatology, and community functioning are unclear, and few studies have compared these relationships amongst patients with affective and non-affective psychoses in the same study. We examined neurocognitive, clinical, and community functioning in a cross-diagnostic sample of patients with psychotic disorders over a 6-month follow-up interval. METHOD: Neurocognitive, clinical and community functioning were assessed in participants with schizophrenia (n=13), schizoaffective disorder (n=17), or bipolar disorder with psychosis (n=18), and healthy controls (n=18) at baseline and 6 months later. RESULTS: Neurocognitive functioning was impaired in all diagnostic groups and, despite reductions in primary symptoms, did not recover on most measures over the follow-up period. Neurocognitive impairment was not associated with diagnosis or clinical improvement. Several neurocognitive scores at baseline (but not diagnosis or clinical baseline or follow-up scores) predicted community functioning at follow-up. DISCUSSION: In one of the few studies to longitudinally examine neurocognition in association with clinical and outcomes variables in a cross diagnostic sample of psychotic disorders patients, neurocognitive deficits were pronounced across diagnoses and did not recover on most measures despite significant reductions in clinical symptoms. Baseline neurocognitive functioning was the only significant predictor of patients’ community functioning six months later. Efforts to recognize and address cognitive deficits, an approach that has shown promise in schizophrenia, should be extended to all patients with psychosis.